Challenges faced by communication providers in meeting regulatory requirements: Analysis of equivalence of input and functional separation - Sinnakkrishnan Perumal; Robert Walker (International Telecommunications Society (ITS), 2014)
Regulatory authorities, governing markets and industries around the world, aim to develop a fair and equivalent competitive market with low entry and exit barriers that provide customers with sufficient knowledge and information to enable them to switch between products, services and suppliers at will. Equivalence of Input (EOI) and Functional Separation (FS) are mechanisms used by telecommunications regulatory authorities to achieve this objective. This paper discusses and analyses legislations mandating the use of EOI and FS, in various geographies, and the challenges that the mechanisms impose on Significant Market Power (SMP) Telco organisations. Furthermore, this paper provides a solution framework for Telco organisations to comprehensively address these challenges in their transformation programmes.
Keywords: 330; Equivalence of Input; Functional Separation; Telecom Regulation; Transformation